Chronic Ethanol During Adolescence Impacts Corticolimbic Dendritic Spines and Behavior. (14th June 2017) - Jury, Nicholas J.; Pollack, Gabrielle A.; Ward, Meredith J.; Bezek, Jessica L.; Ng, Alexandra J.; Pinard, Courtney R.; Bergstrom, Hadley C.; Holmes, Andrew
Abstract : Background: Risk for alcohol use disorders (AUDs) in adulthood is linked to alcohol drinking during adolescence, but understanding of the neural and behavioral consequences of alcohol exposure during adolescence remains incomplete. Here, we examined the neurobehavioral impact of adolescent chronic intermittent EtOH (CIE) vapor exposure in mice. Methods: C57BL/6J‐background Thy1‐EGFP mice were CIE‐exposed during adolescence or adulthood and examined, as adults, for alterations in the density and morphology of dendritic spines in infralimbic (IL) cortex, prelimbic (PL) cortex, and basolateral amygdala (BLA). In parallel, adolescent‐ and adult‐exposed C57BL/6J mice were tested as adults for 2‐bottle EtOH drinking, sensitivity to EtOH intoxication (loss of righting reflex [LORR]), blood EtOH clearance, and measures of operant responding for food reward. Results: CIE during adolescence decreased IL neuronal spine density and increased the head width of relatively wide‐head IL and BLA spines, whereas CIE decreased head width of relatively narrow‐head BLA spines. Adolescents had higher EtOH consumption prior to CIE than adults, while CIE during adulthood, but not adolescence, increased EtOH consumption relative to pre‐CIE baseline. CIE produced a tolerance‐like decrease in LORR sensitivity to EtOH challenge, irrespective of the age at which mice received CIE exposure. Mice exposed to CIE during adolescence, but not adulthood, required more sessions than AIR controls to reliably respond for food reward on a fixed‐ratio (FR) 1, but not subsequent FR3, reinforcement schedule. On a progressive ratio reinforcement schedule, break point responding was higher in the adolescent‐ than the adult‐exposed mice, regardless of CIE. Finally, footshock punishment markedly suppressed responding for reward in all groups. Conclusions: Exposure to CIE during adolescence altered dendritic spine density and morphology in IL and BLA neurons, in parallel with a limited set of behavioral alterations. Together, these data add to growing evidence that key corticolimbic circuits are vulnerable to the effects of alcohol during adolescence, with lasting, potentially detrimental, consequences for behavior. Abstract : The neural and behavioral consequences of alcohol exposure during adolescence remains incomplete. Here, we examined the neurobehavioral impact of adolescent chronic intermittent EtOH (CIE) vapor exposure in C57BL/6J Thy1‐EGFP mice. Exposure to CIE during adolescence altered dendritic spine density and morphology in infralimbic (IL) and basolateral amygdala (BLA) neurons, in parallel with a set of behavioral alterations. Together, these data add to growing evidence that key corticolimbic circuits are vulnerable to the effects of alcohol during adolescence, with lasting, potentially detrimental, consequences for behavior.